Proccedings of International Scientific Conference "BALTTRIB 2017" 2017
DOI: 10.15544/balttrib.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed Oil Versus Soybean Oil – Rheological and Tribological Properties

Abstract: The purpose of this paper is a comparison between rapeseed oil and soybean oil, regarding their rheological and tribological properties. Tests were performed on a Brookfield viscometer with cone-plate geometry, having the following test parameters: test type -shear rate imposed, shear rate (100...2000 s -1 ), temperature values between 20 °C and 75 °C. In parallel, there were proceed tribological tests on a four ball machine, for three speeds (1200, 1500 and 1800 rpm). The results of the tests highlight the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It was found [17] that a mixture with 20% of transesterified vegetable oil and 80% of diesel leads to lower wear on the cylinder. From this point of view, the tribological properties of some vegetable oils become important for obtaining fuel mixtures with improved lubricant properties, since pure oils such as sunflower, rapeseed, and soybean have been proven to have good lubricant properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It was found [17] that a mixture with 20% of transesterified vegetable oil and 80% of diesel leads to lower wear on the cylinder. From this point of view, the tribological properties of some vegetable oils become important for obtaining fuel mixtures with improved lubricant properties, since pure oils such as sunflower, rapeseed, and soybean have been proven to have good lubricant properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Other vegetable oils such as are sunflower oil and soybean oil has the percentage sum of these three fatty acids higher, not at the value of rapeseed oil (Karmakar et al , 2017). Vegetable oils exhibit lower viscosity but high viscosity index (Radulescu et al , 2017; Arnšek and Vizintin, 2000).…”
Section: Methodology For Evaluation the Texture Of Wear Scarsmentioning
confidence: 99%
“…Radulescu et al 9 reported that the friction-reducing and anti-wear performance of SO was better than rapeseed oil at a lower speed (1200 r/min) and load (200 N). Taha-Tijerina et al 10 also illustrated that SO exhibited better performances in friction reducing than corn oil and sunflower oil.…”
Section: Introductionmentioning
confidence: 99%